Educação e ação de governo: análises do ensino público brasileiro - Giacomin, Rafael Luís (2015)
The present study is divided into two articles of which central axis revolves the concern in improving public teaching in Brazil. The first article aimed at identifying the influence of factors susceptible of intervention from public management over proficiency in mathematics of 5 th year students in Brazilian public schools. The second article aimed at investigating the evolution of public expenses in order to identify if social expenses, especially education, were prioritized at any moment within the period from 2000 to 2014. In this sense, we sought to identify, on the one hand, which factors most influence education quality, and on the other, which effort measure the government has performed in recent years to substantiate an improvement in education. The set of results found by means of both articles refers to a positive perspective regarding education in the country, concerning the efforts of public policy.